Scientific and theoretical bases of the system approach to solution of problems of integration of scientific and research work in the university training of the future teachers. (Journal of Educational Sciences, 2016)
The article is devoted to the substantiation and development of the pedagogical system of integration of research and educational work in the process of future teachers’ university training. It is set that the mosteffective decision of this problem can be obtained using the system approach as leading and strategic direction of modern scientific cognition. The author examined the theoretical and historical aspects of the next concepts «system», «system approach», «general theory of the systems», «pedagogical system», and «structure of the pedagogical system». The features of the pedagogical systems and also the basic requirements to their description are pointed out. It is worked out the structure of the pedagogical system of integration of research and educational workof future teachers, which includes components such as target component (aim, tasks, result); subject and object component (teachers and students, their co-operation over a period of integration of research andeducational work); substantive component (the forms of integration of research and educational work of future teachers in the process of university training); technological component (pedagogical technologyof realization of different forms of integration of research and educational work in the process of future teachers’ university training); motivational and incentive component (mechanisms of stimulation of teachersand students to the scientific work). The author points out the concept «Pedagogical system of integration of research and educational work».The aim which needs facilities and methods of its achievement is the basic factor of the pedagogical system of integration of research and educational work. Principles of construction and realization of the pedagogical system are worked out. The pedagogical conditions of integration of university science and education are indicated. Thus, the system approach is identified as the fundamental direction of scientific cognition within the problem of integration of university science and education. It orients on research integrations as a pedagogical system that is certain integrity which consists of components. This co-operation generates new, integrative qualities, which are not the mechanical sum of qualities of its parts. Development of conceptual positions of the pedagogical system of integration of research and educational work in the process of future teachers’university training will become the article of further scientific searches.
Keywords: pedagogical system; integration of research and educational work; university training